ANALISIS KETERBATASAN MEDIA PEMBELAJARAN: TANTANGAN DAN SOLUSI DALAM PEMBELAJARAN KONTEKSTUAL - Yuniarto, Eko; Widayanti, Febi Dwi; Rahayuningsih, Sri; Rahmani, Atika Zulfa; Setya, Clarissa Dwi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the crucial role of instructional media in supporting contextual learning. However, many elementary schools in Malang City still face limitations in media resources. Initial observations found that the use of teaching modules without adequate illustrations makes it difficult for students to understand abstract concepts of geometric shapes. The focus of this research is to analyze these media limitations and identify effective solutions to improve student understanding. This research used a qualitative approach with a case study design, involving students, teachers, and the principal. Data were collected through interviews, observations, document studies, and questionnaires, which were then analyzed using thematic analysis. The results confirmed that the limitations of visual media make it difficult for students to differentiate, illustrate, and draw geometric shapes. The main finding is that the implementation of creative and technological solutions, such as the use of posters, animated videos, the creation of geometric shape miniatures, and GeoGebra software, proved effective in improving student understanding, creativity, and engagement. It is concluded that technological adaptation and a variety of instructional media are crucial for overcoming the limitations of contextual learning of abstract material and developing 21st-century skills. ABSTRAKPenelitian ini dilatarbelakangi oleh krusialnya peran media pembelajaran dalam mendukung pembelajaran kontekstual, namun kenyataannya banyak sekolah dasar di Kota Malang masih menghadapi keterbatasan media. Observasi awal menemukan bahwa penggunaan modul ajar tanpa ilustrasi memadai menyebabkan siswa kesulitan memahami konsep abstrak bangun ruang. Fokus penelitian ini adalah untuk menganalisis keterbatasan media tersebut dan mengidentifikasi solusi efektif untuk meningkatkan pemahaman siswa. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan siswa, guru, dan kepala sekolah. Pengumpulan data dilakukan melalui wawancara, observasi, studi dokumen, dan kuesioner, yang kemudian dianalisis menggunakan analisis tematik. Hasil penelitian mengonfirmasi bahwa keterbatasan media visual menyebabkan siswa kesulitan membedakan, mengilustrasikan, dan menggambar bangun ruang. Temuan utama adalah bahwa penerapan solusi kreatif dan teknologi, seperti penggunaan poster, video animasi, pembuatan miniatur bangun ruang, dan perangkat lunak Geogebra, terbukti efektif meningkatkan pemahaman, kreativitas, dan keaktifan siswa. Disimpulkan bahwa adaptasi teknologi dan variasi media pembelajaran sangat penting untuk mengatasi keterbatasan pembelajaran kontekstual materi abstrak dan mengembangkan keterampilan abad ke-21.